Research of Reasons for Human Development Index Growth by GMDH - Tutova, O.; Savchenko, E. (Індуктивне моделювання складних систем, 2013)
The goal of this paper is modeling of influence of macroeconomic factors on the growth of national income as a component of human development index. Indicators influencing national income growth were analyzed. Models that give possibility to analyze what macroeconomic indicators are the most influential for the national income growth were developed. Also these models enable to assess how national income will change with changing given indicator.